Improving our practice as mathematics teacher educators through teaching research - Liang, Su; Prasad, Priya; Patterson, Cody; Mira, Raquel (International journal for the scholarship of teaching and learning, 2019)
Four mathematics teacher educators from a large, minority-serving university formed a teaching research group in Fall 2016. The goal for this project is to establish a repeated cycle of improving our mathematics content course for pre-service teachers and to contribute a shared knowledge base which rests on foundation of well-defined learning goals in mathematics courses for elementary pre-service teachers. Guide by the Continuous Improvement framework (Berk & Hiebert, 2009), we utilized a data-driven approach to improving teaching, as well as embedding a discussion of classroom implementation into an investigation of an innovation (or, in our case, a mathematical task). In this paper, we present an example of iterative task design for the topic of geometric similarity, we hope to share this as a model of professional development for mathematics teacher educators that highlights the benefits to our students and to ourselves.